PENGARUH KONSERVATISME AKUNTANSI, STRUKTUR MODAL DAN INVESTMENT OPPORTUNITY SET TERHADAP KUALITAS LABA - Sarah Salsabila; Hasanah, Neneng (Jurnal Nusa Akuntansi, 2024)
This study aims to determine the effect of accounting conservatism, capital structure, and investment opportunity set variables on earnings quality variables in basic materials companies in 2018-2022. The independent variables in this study are accounting conservatism, capital structure, and investment opportunity set, the dependent variable is earnings quality. The research method used is a quantitative method, the data sources used are secondary data. The technique used in this study is a purposive sampling technique. The population used in this study are basic materials companies listed on the IDX in 2018-2022. The sample used in this study was 12 company samples with a research observation period of 5 years in the period 2018-2022 and the number of financial reports used as samples in this study was 60. The data analysis technique used was multiple linear regression with the help of the e-views version 12 statistical processing program. The partial test results showed that the accounting conservatism variable had an effect on earnings quality, the capital structure variable had no effect on earnings quality, and the investment opportunity set variable had no effect on earnings quality, while the simultaneous test results showed that the accounting conservatism, capital structure, and investment opportunity set variables simultaneously had a simultaneous effect on earnings quality.